Musculoskeletal manifestations and autoantibodies in children and adolescents with leprosy - Luciana Neder; Daniel A. Rondon; Silvana S. Cury; Clovis A. da Silva (Brazilian Society of Pediatrics, 2014)
Objective: To evaluate musculoskeletal involvement and autoantibodies in pediatric leprosy patients. Methods: 50 leprosy patients and 47 healthy children and adolescents were assessed according to musculoskeletal manifestations (arthralgia, arthritis, and myalgia), musculoskeletal pain syndromes (juvenile fibromyalgia, benign joint hypermobility syndrome, myofascial syndrome, and tendinitis), and a panel of autoantibodies and cryoglobulins. Health assessment scores and treatment were performed in leprosy patients. Results: At least one musculoskeletal manifestation was observed in 14% of leprosy patients and in none of the controls. Five leprosy patients had asymmetric polyarthritis of small hands joints. Nerve function impairment was observed in 22% of leprosy patients, type 1 leprosy reaction in 18%, and silent neuropathy in 16%. None of the patients and controls presented musculoskeletal pain syndromes, and the frequencies of all antibodies and cyoglobulins were similar in both groups (p > 0.05). Further analysis of leprosy patients demonstrated that the frequencies of nerve function impairment, type 1 leprosy reaction, and silent neuropathy were significantly observed in patients with versus without musculoskeletal manifestations (p = 0.0036, p = 0.0001, and p = 0.309, respectively), as well as multibacillary subtypes in leprosy (86% vs. 42%, p = 0.045). The median of physicians' visual analog scale (VAS), patients' VAS, pain VAS, and Childhood Health Assessment Questionnaire (CHAQ) were significantly higher in leprosy patients with musculoskeletal manifestations (p = 0.0001, p = 0.002, p = 0002, and p = 0.001, respectively). Conclusions: This was the first study to identify musculoskeletal manifestations associated with nerve dysfunction in pediatric leprosy patients. Hansen's disease should be included in the differential diagnosis of asymmetric arthritis, especially in endemic regions.